Boosting two-photon photodynamic therapy with mitochondria-targeting ruthenium–glucose conjugates. Issue 43 (24th April 2020) - Liu, Jiangping; Liao, Xinxing; Xiong, Kai; Kuang, Shi; Jin, Chengzhi; Ji, Liangnian; Chao, Hui
Abstract : A series of ruthenium–glucose conjugates was developed to act as two-photon absorption (TPA) PDT agents to effectively destroy tumors by preferentially targeting both tumor cells and mitochondria. Abstract : Herein, we present a series of dual-targeted ruthenium–glucose conjugates that can function as two-photon absorption (TPA) PDT agents to effectively destroy tumors by preferentially targeting both tumor cells and mitochondria. The in vivo experiments revealed an excellent tumor inhibitory efficiency of the dual-targeted TPA PSs.